Consumer attitudes and purchase intentions towards sustainable foods - Veltmann, Leonie Paula (2023)
Purpose: This dissertation examines the effect of sustainability cues on attitudes and ultimately purchase intentions of green products. The study differentiates between extrinsic cues (i.e., recyclable packaging and minimum packaging labels) which are not physically part of the product, and intrinsic cues (i.e., vegan and organic labels) which are integrated into the product. Methodology: More specifically, the methodology involves assessing the influence of perceived attributes on the willingness to purchase and investigating how different cues relatively affect the perceptions of sustainability, taste and healthiness. Finally, the study explores how cues directly influence the purchase intention. Thus, the mediating role of the perceived attributes in the relationship between product cues and willingness to purchase is being investigated. To account for diverse consumption motivations, the analysis distinguished between vice products and virtue, or in other words, unhealthy and healthy products. Findings: The results indicate a significant influence of attribute perception on purchase intention and of cues on these attributes, with extrinsic/intrinsic cues, and vice/virtue products, exhibiting different effects. However, contrary to expectations, a direct impact of the cues on purchase intentions were not observed. Consequently, the study suggests that the mediating role of the perceived attributes in this relationship may not be substantial. Limitations: The findings also indicate limiting factors that could contribute to the absence of these direct effects. Further research is needed to explore these factors and provide a more comprehensive understanding of the complex relationships.